Chivalry of the Chinese Heroes: : A Character Sketch of the Knights-Errant and the Assassins in Sima Qian’s Records of the Grand Historian - Oungbho, Nop (Journal of Sinology (วารสารจีนวิทยา), 2017)
This article looks into a character sketch of the historical knights-errant and assassins as depicted in Sima Qian’s Records of the Grand Historian. Both groups of people are featured in two chapters of the Records, which are ‘Biographies of the Knights-errant’ and ‘Biographies of the Assassins’, respectively, including how they were born to the society, what they did, their social positions and ideals towards their own acts, and how different groups of people thought about them. The article would also discuss the Chinese-style heroism, which has influenced many writers in creating the works of fiction about ‘wuxia’ (martial hero or arrior) in later periods as well.